Autocatalytic Intermolecular versus Intramolecular Deprotonation in CH Bond Activation of Functionalized Arenes by Ruthenium(II) or Palladium(II) Complexes. Issue 23 (17th April 2013) - Fabre, Indira; von Wolff, Niklas; Le Duc, Gaëtan; Ferrer Flegeau, Emmanuel; Bruneau, Christian; Dixneuf, Pierre H.; Jutand, Anny
Abstract The activation of the CH bond of 1‐phenylpyrazole (2) and 2‐phenyl‐2‐oxazoline (3) by [Ru(OAc)2(p‐cymene)] is an autocatalytic process catalyzed by the co‐product HOAc. The reactions are indeed faster in the presence of acetic acid and water but slower in the presence of a base K2CO3. A reactivity order is established in the absence of additives: 2‐phenylpyridine>2‐phenyl‐2‐oxazoline>1‐phenylpyrazole (at RT). The accelerating effect of added acetate ions reveals an intermolecular deprotonation after CH bond activation by a cationic RuII center (SE3 mechanism). The reactions of 1‐phenylpyrazole and 2‐phenyl‐2‐oxazoline first lead to the neutral cyclometalated complexes A2 and A3 ligated by one acetate. The latter dissociate to the cationic complexes B2+ and B3+, respectively, and acetate. A slow incorporation of one or two D atoms into 2, 3, and 2‐phenylpyridine (1) was observed in the presence of deuterated acetic acid. The "reversibility" of the CH bond activation/deprotonation takes place from the cationic complexes Bn+ (n=1–3). They are also involved in oxidative additions to PhI, which are rate‐determining and lead to the mono‐ and bis‐phenylated products at high temperatures. A general mechanism is proposed for the arylation of arenes 1–3 catalyzed by [Ru(OAc)2(p‐cymene)]. In contrast, the reaction of Pd(OAc)2 with 2‐phenylpyridine (1), is much faster: Pd(OAc)2>[Ru(OAc)2(p‐cymene)]. Since the kinetics is not affected by added acetates, the reaction proceeds through a CMD mechanism assisted by a ligated acetate (intramolecular process) and is irreversible. A bis‐cyclometalated PdII^PdII dimer D′1 is formed whose bielectronic electrochemical oxidation leads to a [PdIII^PdIII]2+ dimer, in agreement with the result of a reported chemical oxidation used in arene functionalizations catalyzed by Pd(OAc)2.